2015
DOI: 10.1080/02763893.2015.1055024
|View full text |Cite
|
Sign up to set email alerts
|

“No Home, No Place”: Addressing the Complexity of Homelessness in Old Age Through Community Dialogue

Abstract: The aging-in-place agenda supports the right of seniors to live in their preferred environment, as the place where they can retain a sense of independence and control in old age. This right is compromised for vulnerable seniors who are homeless or at risk of becoming homeless. Causes of homelessness in old age are complex, and pathways into and out of homelessness are multifaceted, including financial insecurity, relationship breakdown, and addiction, compounded by barriers to accessing services, shrinking soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 29 publications
0
17
0
3
Order By: Relevance
“…Researchers have also shown that individuals experiencing homelessness over the age of 50 have serious mental health concerns (Garibaldi, Conde-Martel, & O'Toole, 2005;Joyce & Limbos, 2009) and more frequent hospital admissions and ambulatory care than their younger counterparts (Brown & Steinman, 2013). This group faces additional unique health issues including high rates of physical disability, mobility and sensory limitations, and sometimes dementia (HomelessHub, n.d.; Woolrych, Gibson, Sixsmith, & Sixsmith, 2015). Older homeless adults have a life expectancy that is 15-25 years lower than the general population (Woolrych et al, 2015).…”
Section: Non-financial Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have also shown that individuals experiencing homelessness over the age of 50 have serious mental health concerns (Garibaldi, Conde-Martel, & O'Toole, 2005;Joyce & Limbos, 2009) and more frequent hospital admissions and ambulatory care than their younger counterparts (Brown & Steinman, 2013). This group faces additional unique health issues including high rates of physical disability, mobility and sensory limitations, and sometimes dementia (HomelessHub, n.d.; Woolrych, Gibson, Sixsmith, & Sixsmith, 2015). Older homeless adults have a life expectancy that is 15-25 years lower than the general population (Woolrych et al, 2015).…”
Section: Non-financial Barriersmentioning
confidence: 99%
“…This group faces additional unique health issues including high rates of physical disability, mobility and sensory limitations, and sometimes dementia (HomelessHub, n.d.; Woolrych, Gibson, Sixsmith, & Sixsmith, 2015). Older homeless adults have a life expectancy that is 15-25 years lower than the general population (Woolrych et al, 2015). Metraux and colleagues estimate an average life expectancy of 64 years (Metraux, Eng, Bainbridge, & Culhane, 2011).…”
Section: Non-financial Barriersmentioning
confidence: 99%
“…Por otro lado, respecto a la «estimulación social» (la interacción social, la participación activa y el compromiso social de las personas mayores), constituyen un factor de envejecimiento exitoso y saludable indiscutible. Por ello, son diversos los proyectos tecnológicos que proponen webs y blogs sociales, proyectos de mentoria social apoyados en plataformas virtuales, redes sociales, etc., que buscan garantizar un envejecimiento realmente activo, optimizando las oportunidades de salud, participación y seguridad y, en definitiva, mejorar la calidad de vida a medida que las personas envejecen (oms, 2012;Sixsmith, 2013Sixsmith, , 2015.…”
Section: El Papel Educativo De La Tecnología (Digital) En La Vejezunclassified
“…De este modo, el desarrollo de la revolución digital, que afecta prácticamente a todas las esferas de la vida humana, desempeña un papel fundamental en el cambio de ese modelo, a favor de una visión de la vejez activa, saludable y comunitariamente participativa (McCreadie y Tinker, 2005;Sixsmith, 2013;Woolrych, Gibson, Sixsmith y Sixsmith, 2015). Por este motivo, el mayor o menor uso de determinados dispositivos en cualquier faceta de la vida de los mayores, así como la facilidad de conectividad y ubicuidad que presentan, está conduciendo a muchos investigadores a analizar procesos de rutinización de la tecnología vinculados al envejecimiento.…”
unclassified
“…Based on the studies that tackle this issue, it is clear that quality of life in old age depends on lifelong interactions and many elements, such as longevity, biological health, mental health, satisfaction, cognitive control, social competence, productivity, activity, efficacy cognitive, social status, income, the continuity of family and occupational roles, and continuity of informal relationships with friends 31 .…”
mentioning
confidence: 99%